PENGARUH KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN MIE INDOMIE GORENG (STUDI KASUS MAHASISWA MANAJEMEN ANGKATAN 2016 UNIVERSITAS MUHAMMADIYAH PAREPARE) - Mardianah, Mardianah; Idrus, Irwan (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2021)
This study aimed to examine of product quality and promotion on purchasing decisions of instant noodles-Indomie Goreng. The research sample was management students class 2016 Universitas Muhammadiyah Parepare. Data collected using the questionnaire method with a total sampling of 60 students. Furthermore, the data were analyzed using statistical data processing with multiple linear regression models. The results showed that: 1) Product quality does not affect purchasing decisions, 2) Promotion affects purchasing decisions.